(untitled) (UNED Research Journal, 2015)
The Corrosion maps used are to display quickly the different situations in a country. These maps developed are for low alloy steel in Costa Rica depending on climatic data and pollutant levels, considering the different regulations associated with ISO 9223 and models developed by the Center for Research in Corrosion (CICorr). The atmosphere in Costa Rica has high rates of Brooks, considered very corrosive. The corrosion controlling atmospheric parameters are the relative humidity (RH) and Wetting Time (TWH) associated with low levels of pollution and rural type atmospheres. The corrosion rates are between 25 and 80μm*yr-1 (Class 3 and 4 according to ISO 9223). Local models associated with the controlling parameters are more suitable for estimating the corrosion according to ISO 9223.